2022
DOI: 10.1029/2022jc018572
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Four Types of Baroclinic Instability in the Global Oceans

Abstract: Distinct geographical distributions of four types of mesoscale baroclinic instabilities (BCIs) exist in the global oceans, implying preferences of surface or subsurface mesoscale eddies to specific regions. This study explores seasonal variations of global BCI types and their dependence on varying background ocean states with a focus on three representative regions. First, the regions of the Kuroshio Extension and Gulf Stream are representative for distinctive seasonal transition of BCI types: the Charney surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…(2021), Feng et al. (2022) and Hochet et al. (2015), who found that in this latitudinal band (8°–18°N) the fastest‐growing baroclinic instability is subsurface‐intensified and is generated by interaction of a pair of counter‐propagating second baroclinic Rossby waves.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…(2021), Feng et al. (2022) and Hochet et al. (2015), who found that in this latitudinal band (8°–18°N) the fastest‐growing baroclinic instability is subsurface‐intensified and is generated by interaction of a pair of counter‐propagating second baroclinic Rossby waves.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, according to the common vertical scale and structure of the sub-thermocline ISVs in this region (Figure S2 in Supporting Information S1), the WVD likely is the second baroclinic mode-like Rossby wave-initiated instability wave. This can be indicated by Feng et al (2021), Feng et al (2022 and Hochet et al (2015), who found that in this latitudinal band (8°-18°N) the fastest-growing baroclinic instability is subsurface-intensified and is generated by interaction of a pair of counter-propagating second baroclinic Rossby waves. Whereas, due to complicated top and bottom boundary conditions and mean flows, how well this baroclinic mode fits a normal second baroclinic mode needs further studies.…”
Section: Dynamical Properties Of the Wvdmentioning
confidence: 86%
See 2 more Smart Citations
“…The coupling of buoyancy and shear is widespread in atmospheric motion and oceanic flow (Deardorff 1972;Khanna & Brasseur 1998). For example, the surface mesoscale eddies in the ocean are generated mainly by baroclinic instabilities, which are relevant to the pole-equator temperature gradient and a vertical shear (Hopfinger & van Heijst 1993;Pierrehumbert & Swanson 1995;Vincze et al 2014;Feng et al 2022). There are very many attempts to combine shear and buoyancy in one system and study their coupling effect.…”
Section: Introductionmentioning
confidence: 99%